ENCAPSULATION OF HYDROXYAPATITE EGGSHELL in Ca-ALGINATE for Cd(II) ADSORPTION - Martini, Sri
Cadmium is a toxic metal that could cause nausea, diarrhea, muscle cramps, kidney degradation and chronic lung disorders if accumulated in the body. Cadmium is frequently used as a primary or additional material in nickel-cadmium batteries industry, pigmentation, coatings, stabilizers in the plastics industry and other synthetic materials. The common methods used to remove a heavy metal are precipitation, ion exchange, solvent extraction, ultra-filtration, reverse osmosis, electrodialysis, and adsorption. Adsorption process is an effective method to remove a heavy metal from the wastewater. Hydroxyapatite (HAP) derived from chicken eggshell is an adsorbent which can be used to remove the metal ion contamination. In this study, HAP was encapsulated in Ca-alginate (Ca-A) thus obtained grains of Ca-alginate microcapsules containing hydroxyapatite (Ca-HAP) that was used as Cd(II) ion adsorbent. HAP derived from chicken eggshells was synthesized by the sol-gel method. The result of hydroxyapatite synthesis were characterized by XRD and FTIR. Several groups identified in the FTIR are PO43-, CO32- and OH-. Based on the results of X-ray diffraction, the diffraction pattern of hydroxyapatite of the sample produced appropriate to the diffraction pattern of JCPDS (Joint Committee on Powder Diffraction Standards) hydroxyapatite number 1306-06-5. The optimal conditions for adsorption of metal ion Cd(II) by Ca-A, and Ca-HAP with the batch method was performed by varying the pH, contact time, the initial concentration of Cd(II), and the adsorbent mass. The pH values, contact time, and the mass of adsorbent in the optimal conditions for both of the adsorbent are respectively at pH 4, 6 hours and 0.15g. The maximum adsorption capacities of the ion Cd(II) by Ca-A, and Ca-HAP are 90.07mg/g and 81.35mg/g. The adsorption process of Cd(II) by both of adsorbents is according to the Langmuir isotherm adsorption model. Adsorption kinetic for both of adsorbents followed the second-order pseudo adsorption kinetic model. Binary system adsorption was conducted by the batch method using Cd(II), Pb(II), Zn(II), Cu(II) metals and Ca-HAP adsorbent is known that not selective to one of metals. Study of Ca-HAP adsorbent column was conducted by circulation method and the minimum time to adsorb all of Cd(II) ions is 6.5 hours. Desorption process used 30 ml of HNO3 1M and produced of 84.17% desorption efficiency (n =3). Cd(II) ion recovery by adsorption-desorption process in environmental samples was obtained 76.46%. This percentage recovery result indicates that the presence of a matrix in environmental samples that affect to adsorb performance Cd(II) ions of Ca-HAp adsorbent.